2016
DOI: 10.1038/srep29993
|View full text |Cite
|
Sign up to set email alerts
|

A Superamphiphobic Sponge with Mechanical Durability and a Self-Cleaning Effect

Abstract: A robust superamphiphobic sponge (SA-sponge) is proposed by using a single initiated chemical vapor deposition (i-CVD) process. Poly(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl methacrylate) (PFDMA) is deposited on a commercial sponge by the polymerization of fluoroalkyl acrylates during the i-CVD process. This PFDMA is conformally coated onto both the exterior and interior of the sponge structure by a single step of the i-CVD process at nearly room temperature. Due to the inherent porous structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In contrast to the aforementioned two strategies, a one‐pot method is deemed to be simpler for the fabrication and thereby has frequently been studied . Recently Lin et al applied an in situ one‐step vapor phase polymerization method to prepare electrically conductive superamphiphobic fabrics with polypyrrole in conjunction with fluorinated alkylsilane .…”
Section: Fabrication Methods For Superamphiphobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the aforementioned two strategies, a one‐pot method is deemed to be simpler for the fabrication and thereby has frequently been studied . Recently Lin et al applied an in situ one‐step vapor phase polymerization method to prepare electrically conductive superamphiphobic fabrics with polypyrrole in conjunction with fluorinated alkylsilane .…”
Section: Fabrication Methods For Superamphiphobicitymentioning
confidence: 99%
“…Additionally, a facile one‐step i‐CVD route has been developed by Kim et al to fabricate a robust superamphiphobic coating on a sponge surface, in which no additional solvent was required, thereby resulting in an all‐dry vapor‐phase process . By such a single simple step of the i‐CVD process, the poly(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10‐heptadecafluorodecyl methacrylate) was successfully deposited onto both the interior and exterior of the sponge structure relying on the polymerization of fluoroalkyl acrylates ( Figure ).…”
Section: Fabrication Methods For Superamphiphobicitymentioning
confidence: 99%
“…Kim et al reported on a superamphiphobic sponge of outstanding mechanical durability that has self‐cleaning effects while preserving its own complex structure as a sponge . A polymer film containing a perfluoroalkyl chain, poly(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10‐heptadecafluorodecylmethacrylate) (pPFDMA), was conformally deposited onto a sponge including the inner surface of the sponge structure.…”
Section: Icvd For Surface Treatmentsmentioning
confidence: 99%
“…a) A snapshot image of various ink‐dyed liquid droplets (water: blue‐B, mineral oil: white‐W, dodecane: yellow‐Y, hexadecane: red‐R) on the superamphiphobic sponge. The inset image shows the same liquid droplets on the bare sponge . b) SEM and AFM images of the non‐coated polyester fabric surface (left), the slightly rough surface of p(V4D4‐L‐PFDA) coated fabric (middle), the rougher surface of the p(V4D4‐L‐PFDA) coated fabric (right) .…”
Section: Icvd For Surface Treatmentsmentioning
confidence: 99%
“…We do believe that the inorganic core of our 3D structure provides a high stability. Kim et al prepared a superhydrophobic sponge (totally organic based material) using iCVD, where both 3D porous core structure and coated layer are both organic . Our 3D hybrid structure (PTFE: organic layer and TiO 2 : inorganic skeleton) seems to resist chemical and physical environment better.…”
mentioning
confidence: 96%